Pediatric facial fracture in Garhwal Himalayan Region of Uttarakhand State: A retrospective study - Amit Shah; Vikas Sikarwar; Ankur Joshi; Nidhi Singh; Anshdeep Singh; Shailee Kardam (Journal of Pharmacy and Bioallied Sciences, 2024)
Background: Pediatric facial fractures are fairly uncommon injuries and comprise less than 15% of all facial fractures in the literature. Objectives: To analyze the pattern of pediatric facial fractures and compare the results with similar studies performed in India and the rest of the world. Materials and Methods: A total of 231 patients were admitted for the treatment of maxillofacial fractures. Data on etiology, anatomical location, mode of treatment, duration of stay, and X-ray advice were recorded. Results: Pediatric trauma comprised 27% of the total population. The most common cause of injury was road traffic accident (RTA), that is, 28 (43.8%) patients. Conclusion: The incidence of pediatric facial trauma is high in the hilly Garhwal–Himalayan region of Uttarakhand state in India as compared to other states of India.